Dampak Pertumbuhan Aset Perusahaan, Profitabilitas dan kebijakan Hutang terhadap Kebijakan Dividen pada Masa Pandemi Covid-19 : Studi Kasus Perusahaan yang Listing dalam LQ45 di bursa Efek Indonesia Periode 2017-2020 - Purwanti Purwanti (STIM LASHARAN JAYA MAKASSAR, 2022)
The dividend policy reflects the quality and reputation of the company. In practice, during the COVID-19 pandemic, the company had difficulties in determining and deciding on a dividend policy, namely the decision to retain profits to be used as the company's operational development or to distribute dividends to shareholders to increase investor confidence in the company. This study aims to determine the growth of company assets, profitability, and debt policy on dividend policy during the COVID-19 pandemic (a case study of companies listed in LQ45 on the Indonesia Stock Exchange for the 2017-2020 period). The method used is panel data regression analysis with a significance level of 5% in the form of explanatory data analysis data. Sampling based on purposive sampling method amounted to 22 companies, in order to obtain 88 sample data. Based on the results of data analysis, it shows that partially (1) Company Asset Growth (GROWTH) and (2) Debt Policy (DER) have a negative and insignificant effect on Dividend Policy (DPR), (3) Profitability (ROA) has a positive and significant effect on Dividend Policy. (4) Growth of Company Assets, Profitability, and Debt Policy have a significant simultaneous effect on the Dividend Policy. Based on the coefficient of determination (Adjusted R²) the variables in this study contributed 29.35%, the rest was influenced by other factors outside of the research variables.